2020
DOI: 10.1002/pca.2896
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of endemic sixAstragalusspecies by combined NMR and GC‐MS analysis

Abstract: Introduction Astragalus anthylloides, A. dipsaceus, A. karamasicus, A. lycius, A. sigmoideus and A. xylobasis var. angustus are an endemic and generally grow in the Irano‐Turanian phytogeographic region of Turkey. Astragalus species contain saponins, polysaccharides, and phenolics, while the toxic compounds include imidazoline alkaloids, nitro toxins, and selenium derivatives. Objectives To apply a combined metabolomic fingerprinting approach by nuclear magnetic resonance (NMR) and gas chromatography‐mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Compound 52 generating a molecular ion [M–H] − at m/z 279.44 and a fragment ion in MS/MS spectrum at m/z 261.42 due to loss of H 2 O, was identified as linoleic acid, while compound 53 with an extra 15.03 Da was characterized as linoleic acid methyl ester. Meanwhile, compound 48 producing molecular ion at m/z 277.42 and a fragment ion at m/z 259.4, which are 2 Da lower than those of linoleic acid, was proposed to be linolenic acid 34 , 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 52 generating a molecular ion [M–H] − at m/z 279.44 and a fragment ion in MS/MS spectrum at m/z 261.42 due to loss of H 2 O, was identified as linoleic acid, while compound 53 with an extra 15.03 Da was characterized as linoleic acid methyl ester. Meanwhile, compound 48 producing molecular ion at m/z 277.42 and a fragment ion at m/z 259.4, which are 2 Da lower than those of linoleic acid, was proposed to be linolenic acid 34 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Compound 54 showed fragment ions at 264.45 [M- 31.03] − due to loss of methoxy group, and at m/z 221.4 corresponding to loss of McLafferty ion which is characteristic to methyl esters 34 . Meanwhile, compound 56 , with a respective mass of m/z 339.58 [M−H] − , was annotated as behenic acid with MS 2 fragment ions appearing at m/z 321.56 and 295.57 suggestive for the loss of H 2 O and CO 2 , respectively 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these findings, a previous study showed that the EOs of most Astragalus species contained phytol, eicosane, and hexadecanoic acid. [19] Other constituents such as palmitic acid (hexadecanoic acid) and linolenic acid [23] reportedly existed in the EOs of most Astragalus species. Phthalate, as a lipophilics compound, was found in A. adscendence (59.88 %) (Table 1).…”
Section: Essential Oils Analysismentioning
confidence: 99%
“…LC-MS-based metabolomics approaches are widely used to profile complex biological extracts such as those from plants (Shimizu et al, 2018;Feussner and Feussner, 2019), being of particular importance for non-targeted plant metabolomics, mainly due to the plant kingdoms' rich metabolite diversity (Gorrochategui et al, 2016;Wang et al, 2019). Compared to other analytical techniques, the main advantages of LC-MS are that it can cover a wide chemical diversity and a wide dynamic range; it is a complementary analytical technique to nuclear magnetic resonance (NMR) and gas chromatography-MS in metabolomics studies (Anderson et al, 2020;Yaglioglu et al, 2020). The traditional untargeted LC-MS device consists of an LC with a reverse-phase chromatography (RPC) column (with an inner diameter of 2.1 or 4.6 mm) for analyses in front of a mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%